QFD and TRIZ integration in product development: a Model for Systematic Optimization of Engineering Requirements - Ricardo Manfredi Naveiro; Vinicius Motta de Oliveira (Production)
Abstract Paper aims Proposal of a Model for Systematic Optimization of Engineering Requirements applied to product concept development and based on a two-level integration of the methods Quality Function Deployment (QFD) and Theory of Inventive Problem Solving (TRIZ). Originality Requirements extraction directly from patent documents in order to identity the most relevant user requirements as well as the technical requirements interactions through a QFD matrix. Then, TRIZ Contradiction Matrix is used to withdraw the requirements contradictions through inventive principles in order to enable the product conception. Research method Case Study which enables the Model construction inductively through its application on the development of a mortar ammunition concept. Main findings A product concept comprising innovative features which reflect the laws of technology evolution from TRIZ. Implications for theory and practice The product concept definition points to the academic relevance of an integration model which identify the technical requirements objectively from patent documents.